EFFECTIVE STRATEGIES TO ENHANCE RECEPTIVE LANGUAGE SKILLS: LISTENING AND READING - Eshniyozova Gulhida Suvon kizi (Bright Mind Publishing, 2025)
Receptive skills, namely listening and reading, are foundational in second language acquisition, as they enable learners to comprehend and process input before producing language. This paper investigates effective instructional strategies to develop these skills at intermediate to advanced proficiency levels. Through a combination of authentic materials, task-based activities, and metacognitive scaffolding, learners can improve comprehension accuracy, vocabulary range, and learner autonomy. A qualitative study was conducted with two learner groups over eight weeks, comparing traditional form-focused drills with learner-centered, content-rich approaches. Results demonstrate that authentic, interactive methods yield significantly higher gains in both listening and reading comprehension. Implications for classroom practice and future research are discussed.
Keywords: Receptive skills; listening; reading; authentic materials; task-based learning; learner autonomy